DETERMINANTS OF DEBT POLICY IN CONSUMER GOODS COMPANY IN INDONESIA - Bangun, Nurainun; Natsir, Khairina; Ngadiman , Ngadiman (International Journal of Application on Economics and Business, 2023)
The intended of this study was to determine the effect of business risk, non-debt tax shields, and firm size on debt policy. The population consists of companies that in the 2019-2021 period are listed on the Stock Exchange in the consumer goods group. Purposive sampling technique was applied to select samples from as many as 74 companies, of which 40 consumer goods companies met the criteria, so that in total there were 120 research data. Data analysis was carried out using Multiple Linear Regression and data processing data is supported by EViews 12. The findings of this research show that changes in company size will move debt policy in a significant and positive direction. Meanwhile, business risk and nonndebt taxxshields have insignificant effect on debttpolicy for companies in the consumerrgoods group registered on the Indonesia StockkExchange.